Alternative Energy from Cow Dung Waste to An Independent and Creative Community - Deliana; Sofia Hanafiah, Diana; Pohan, Riko Andika (Talenta Publisher, 2021)
Rural communities often pay less attention to cow dung waste and its handling, as well as environmental preservation and environmental health. For rural communities, cow dung waste is considered of no value and is often underestimated. In the cattle farmer community, they almost do not care about their cow dung waste and they usually make it into compost for plant biological fertilizer. In fact, there are other alternatives that can be used as alternatives to energy and can also be economically valuable from materials that are underestimated by the community. Apparently, cow dung waste has a gas that can be reactivated when mixed with the right ingredients. Besides having an unpleasant smell, cow dung waste can also pollute the environment. Therefore, it is a challenge to be able to process cow dung waste into useful materials and make rural communities more creative, productive, and independent. In addition, it is hoped that the processing of cow dung waste can be used as a solution in an effort to make the village environment more beautiful and healthier. The processing of cow dung waste is considered important and useful, so the community service team provided information about making biochar from cow dung waste which can be used as an alternative energy substitute for charcoal. In addition, the community service team also taught the cattle farmer community about the importance of maintaining a clean environment and the dangers caused by cow dung waste.